(2x-p)(3x+2)=6x²+5x+q求P,q

来源:学生作业帮助网 编辑:作业帮 时间:2024/07/12 23:17:25
(2x-p)(3x+2)=6x²+5x+q求P,q
x)0-06Ҵ5PS646.|)@&H";̊305.Ь5*A@:@qg Ov/U(57$Asp;l5L{:@ ]-F00"w38 $Y聀(4@b|=n.( *ARdE@?m$ pB[3$7

(2x-p)(3x+2)=6x²+5x+q求P,q
(2x-p)(3x+2)=6x²+5x+q求P,q

(2x-p)(3x+2)=6x²+5x+q求P,q
(2x-p)(3x+2)=6x^2+(4-3p)x-2p=6x^2+5x+q..4-3p=5,q=-2p,所以 p=-1/3,q=2/3

(2x-p)(3x+2)=6x²+5x+q
6x²+(4-3p)x-2p=6x²+5x+q
所以
4-3p=5
-2p=q

p=-1/3
q=2/3

(2x-p)(3x+2)=6x²+5x+q
6x^2+(4-3p)x-2p=6x²+5x+q
4-3p=5
p=-1/3
q==-2p=-2*(-1/3)=2/3

解;原式=6x²-(4+3px)-2p=6x²+5x+q
-(4+3px)=5x 得出p=-3
-2p=q 得出q=6